Through the eyes of the beholder: the Holy Land, 1517-1713 - Hayden, Judy A.; Matar, Nabil I. (Islamic history and civilization, 2013)
Preliminary Material -- 1. Introduction: Pilgrims and Travelers – In Search of the ‘Holy’ in Holy Land /Judy A. Hayden and Nabil I. Matar -- 2. An Arabic Orthodox Account of the Holy Land, c. 1590s /Nabil I. Matar and Mohammad Asfour -- 3. Early Modern Russian Pilgrims in the Holy Land /Galina I. Yermolenko -- 4. Textual Truths and Lived Experience. George Sandys’s A Relation of a Journey begun an: domini 1610 and William Biddulph’s The Travels of certain Englishmen /Julia Schleck -- 5. Rescuing the Holy Land in Friar Jean Boucher’s Bouquet sacre compose des plus belles fleurs de la Terre sainte /Richard Coyle -- 6. Evliya Çelebi’s Seyahatname and the Holiness of Jerusalem /Hasan Baktir -- 7. Joseph Besson, French Nationalism and Possessing the Holy Land: In Defense of the Jesuit Missionary Enterprise in Greater Syria, 1625–1660 /Mazin Tadros -- 8. Cornelis de Bruyn: Painter, Traveler, Curiosity Collector—Spy? /Judy A. Hayden -- 9. The Sufi and the Chaplain: ‘Abd al-Ghanī al-Nābulusī and Henry Maundrell /Nabil I. Matar -- 10. Early Modern Jewish Prayer in and for Israel /Michael Rotenberg-Schwartz -- 11. A Lutheran in the Holy Land: Michael Eneman’s Journey, 1711–12 /Joachim Östlund -- 12 Conclusion /Nabil I. Matar -- Index.